Adoption and Impact of Climate Information Services Dissemination Platform on Farmers’ Yield, Income and Food Security in Mali - Diallo, Aboubacar; Suh, Neville; Dossou-Yovo, E. R (2024)
The AICCRA Mali project aimed to enhance climate resilience among rice farmers in Mali through climate adaptation initiatives, including climate information services (CIS) platforms such as WhatsApp, mobile phones, and radios. Between 2021 and 2024, 412,038 rice farmers (242,922 males and 169,116 females) were trained and provided with backstopping on using these platforms. The study found that adopting WhatsApp platforms led to increased rice yields (2109 kg/hectare), income from rice sales (653,009 FCFA/hectare), and food consumption scores (11). Mobile phone adopters saw a 600 kg/hectare yield increase, 533,696 FCFA/hectare income increase, and food consumption score of 11. Radio platform users experienced a 608 kg/hectare yield increase, 227,185 FCFA/hectare income increase, and a food consumption score of 12. The study also identified several factors influencing the adoption of CIS platforms. Policies aimed at improving farmers' access to these platforms are crucial for boosting climate resilience by increasing yields, income, and food security.